Absoluteness of Quranic Beauty - Al-Bakush, Moftah Mohamed Mohamed Omar (Journal of Arabic Language Sciences and Literature, 2022)
The concept of beauty in the Qur’an did not limit his attention milestones Hassan and beauty in the world and the Hereafter beauty sensuous but extended this care to the beauty moral than human beauty above beauty and this Mmaidl that the Qur’an method has its own different methods Arab rhetoric and rhetoric and composition. Dealt with this paper exaggeration Beauty Qur’anic where the Qur’an beautiful than all the beauty and charm of dazzling beauty eyes came every verse of the verses carry under their meanings of cosmic very beauty and splendor, we have deficits scholars of rhetoric and imagination to produce the like Quran came and papers of this article illustrated and much of the failure to meet the Qur’anic expression of beauty eloquent endless wonders do not cease because the Qur’an splendor of his eloquence and alignment of the letters arrived to the top of the miracles in all fields of literary and rhetorical. That the main thing in the miracle of the Qur’an is Mizar which of eloquence and rhetoric and the statement, and splendor of meanings and accuracy of harmony words in their buildings, and formatting commensurate with the sweetness of style and quality in the sense, then tightened in the link so that seizes on the feelings of the listeners of this Quran. The method in the Qur’anic text features swab scenic wonder, is reflected in the systems voice quality foundries in conjunction words and sentence and verses and Surat to be reached proficiency in the discharge of speech and Arts Rhetoric can not rhetoricians and spare breaths talented eloquent, coloring Qur’anic discourse was an art of arts likeness stylistic whole by linguists and the people of the ancient and modern statement blessed be God’s best creators.